FROM ONW-WORD SPEECH TO MULTIWORD SPEECH - Carranza Carnicero, José Antonio; Escudero Sanz, Alfonso José; Brito de la Nuez, Alfredo G. (Anales de Psicología / Annals of Psychology)
This paper analyzed the aspects involved in the transition from one-word speech to multi-word utterances. First, the functional vs. structural nature of single-word utterances is discussed, particularly in relation to the first twoword combinations. It is emphasized both the paradoxical character of the concept of "holophrase" and its controversial value as explanatory hypothesis. Then, some alternative proposals regarding the processes and strategies that infants use at the beginning of the two-word speech are considered. It is concluded that there seems to be more than one route to access to multi-word speech. The adopted routes depend on the infants' use of their social-cognitive abilities to make sense the linguistic stimuli accompanying their everyday events and in their need of communicating them in the interactions with others.